2015
DOI: 10.1101/gad.269415.115
|View full text |Cite
|
Sign up to set email alerts
|

A majority of m6A residues are in the last exons, allowing the potential for 3′ UTR regulation

Abstract: We adapted UV CLIP (cross-linking immunoprecipitation) to accurately locate tens of thousands of m 6 A residues in mammalian mRNA with single-nucleotide resolution. More than 70% of these residues are present in the 3 ′ -most (last) exons, with a very sharp rise (sixfold) within 150-400 nucleotides of the start of the last exon. Two-thirds of last exon m 6 A and >40% of all m 6 A in mRNA are present in 3 ′ untranslated regions (UTRs); contrary to earlier suggestions, there is no preference for location of m 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

52
877
6
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 732 publications
(939 citation statements)
references
References 75 publications
52
877
6
4
Order By: Relevance
“…N 6‐methyladenosine (m 6 A) is the most prevalent internal mRNA modification found in eukaryotes, and has received a burst of interest in recent years (Meyer & Jaffrey, 2014; Fray & Simpson, 2015; Yue et al ., 2015). m 6 A appears to be involved in a broad range of biological processes including mRNA export from the nucleus (Fustin et al ., 2013), regulation of splicing (Alarcón et al ., 2015b; Haussmann et al ., 2016; Lence et al ., 2016), mRNA translatability and stability (Wang et al ., 2014a,b, 2015; Bodi et al ., 2015; Zhou et al ., 2015), alternative polyadenylation site choice (Ke et al ., 2015) and other mechanisms accompanying RNA maturation (Meyer & Jaffrey, 2014; Yue et al ., 2015). m 6 A is essential for the earliest stages of pattern formation in plants (Zhong et al ., 2008; Bodi et al ., 2012; Shen et al ., 2016) and metazoans (Meyer & Jaffrey, 2014; Geula et al ., 2015; Yue et al ., 2015; Haussmann et al ., 2016; Lence et al ., 2016), linked with diseases in humans and other mammalian species (Jia et al ., 2011; Zheng et al ., 2013) and is required for meiosis in Saccharomyces cerevisiae (Clancy et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…N 6‐methyladenosine (m 6 A) is the most prevalent internal mRNA modification found in eukaryotes, and has received a burst of interest in recent years (Meyer & Jaffrey, 2014; Fray & Simpson, 2015; Yue et al ., 2015). m 6 A appears to be involved in a broad range of biological processes including mRNA export from the nucleus (Fustin et al ., 2013), regulation of splicing (Alarcón et al ., 2015b; Haussmann et al ., 2016; Lence et al ., 2016), mRNA translatability and stability (Wang et al ., 2014a,b, 2015; Bodi et al ., 2015; Zhou et al ., 2015), alternative polyadenylation site choice (Ke et al ., 2015) and other mechanisms accompanying RNA maturation (Meyer & Jaffrey, 2014; Yue et al ., 2015). m 6 A is essential for the earliest stages of pattern formation in plants (Zhong et al ., 2008; Bodi et al ., 2012; Shen et al ., 2016) and metazoans (Meyer & Jaffrey, 2014; Geula et al ., 2015; Yue et al ., 2015; Haussmann et al ., 2016; Lence et al ., 2016), linked with diseases in humans and other mammalian species (Jia et al ., 2011; Zheng et al ., 2013) and is required for meiosis in Saccharomyces cerevisiae (Clancy et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that m 6 A modifications have different effects on mRNA translation when the m 6 A modifications occur at different regions of the mRNAs (14 -16). RNA methylation at the 5Ј UTR could promote mRNA translation, whereas RNA methylation at the last exons participated in the 3Ј UTR regulation of mRNAs (15,16 other cellular events such as cell differentiation and RNA degradation (17). As transcription is silenced in fully grown oocytes and early embryos, mRNA translation regulation is essential for biological events during this period.…”
mentioning
confidence: 99%
“…It has been shown that m 6 A modifications have different effects on mRNA translation when the m 6 A modifications occur at different regions of the mRNAs (14 -16). RNA methylation at the 5Ј UTR could promote mRNA translation, whereas RNA methylation at the last exons participated in the 3Ј UTR regulation of mRNAs (15,16 …”
mentioning
confidence: 99%
“…Highly specific m 6 A antibodies (Munns and Sims 1975) only became commercially available after 2010, allowing precipitation of m 6 A-containing mRNA fragments followed by sequencing of the precipitated fragments. The initial sequencing experiments showed wide distribution of m 6 A residues in mRNA (Meyer et al 2012;Dominissini et al 2012) with a heavy concentration in the last exon (Ke et al 2015) not close to (within ~50 nucleotides) of a STOP codon but mostly in the 3ʹ UTR (untranslated region). These latter experiments examined RNA that was UV cross-linked to anti-m 6 A antibody followed by (Bhatt et al 2012) laboratories then traced the formation of seven toxin-induced mRNAs in macrophages from nascent RNA to a nucleoplasmic fraction and then to the cytoplasm, establishing an accurate time course and the extent of processing in each fraction.…”
mentioning
confidence: 99%